PROBLEMATICS OF IMPLEMENTING THE INDEPENDENT LEARNING CURRICULUM IN LEARNING ISLAMIC RELIGIOUS EDUCATION AT SMA NEGERI 12 MEDAN - Muhammad Nuzulul Qur'ani; Hasan Basri; Hilman Rizky Hasibuan (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2023)
The Independent Learning Curriculum has become an important topic in the world of education, which offers a new paradigm that focuses on flexibility, adaptability and student empowerment in the learning process. This concept is full of potential and dynamic, its implementation in various educational contexts faces a number of common problems. This study aims to find out how the implementation of the independent learning curriculum, find out the problems faced in the implementation of the independent learning curriculum, and find out how the form of assessment of Islamic religious education learning based on the independent curriculum at SMA Negeri 12 Medan. This research is a field research using descriptive qualitative method. Collecting data in this study using interviews, observation and documentation. Analysis techniques use: data reduction, data visualization, and drawing conclusions/verification. Meanwhile, the data validity test takes the form of source triangulation and technical triangulation. The results of the research showed that the learning of Islamic religious education in the independent learning curriculum at SMA Negeri 12 Medan was fully handed over to teachers and students. Teachers are given freedom in making lesson plans, such as using strategies, methods, media and learning approaches. The problems of learning Islamic religious education in the independent learning curriculum are: teachers still have difficulties in developing independent learning-based learning, incomplete facilities, teachers are comfortable with the 2013 curriculum and inadequate human resources. Meanwhile, the teacher's strategy in implementing the curriculum takes the form of: formulating learning objectives, determining teaching and learning activities, determining tools and materials for learning, planning evaluation of Islamic religious education learning.